Ocurrence and physiological parameters of freshwater stingrays from the Uatumã river basin in the Amazon - Gomes, Maria Fernanda da Silva (2024)
Freshwater stingrays are naturally endemic to South America, and the Amazon region is home to the most incredible diversity; however, areas still lack biological information about this group of elasmobranchs, including the Uatumã River, Amazonas, Brazil. The present work aims to establish the occurrence and physiological parameters of four freshwater stingrays from the Uatumã river basin, Amazonas, Brazil. To this end, stingray collections were carried out in three municipalities bathed by the Uatumã River: Presidente Figueiredo, Itapiranga and São Sebastião do Uatumã. The stingrays were captured through fishing using a hand net, and after capture, the rays were anesthetized, and blood was collected to determine erythrogram and plasma biochemistry values. After blood collection, the captured specimens were identified based on the disc's dorsal and ventral color pattern, the presence or absence of the labial groove and the row of spines on the tail; they were also measured, weighed and sexed. In total, 69 freshwater stingrays were captured, 59 of which were from the Potamotrygon genus and ten from the Paratrygon genus. Most of the individuals captured were young, and the most common species was Potamotrygon orbignyi, which had a reticulated color pattern. Regarding physiological parameters, the values found for the erythrogram and plasma biochemistry were similar to those found in other studies in the Amazon basin. This study provides essential information about the biology of four freshwater stingrays found in the Uatumã river basin, contributing to scientific knowledge, management and conservation of these species, which are fundamental to the Amazon aquatic ecosystem.